MEIOSIS: HOW TO HALVE THE CHROMOSOME NUMBER - A. A. Torgasheva (Вавиловский журнал генетики и селекции)
The notion of meiosis has been changed and refined for over a century since the discovery of this complicated way of cell division. Its success depends on precise time and space orchestration of many processes, such as chromosome replication, packaging, exchange of homologous regions, alignment in the plane of division, and disjunction. The development of molecular and immunocytochemical methods in recent decades cast light on the details of these processes and brought scientists closer to the understanding of mechanisms regulating them. This review presents the current notion of the major meiotic events by examples of yeast and mammals. Particular attention is paid to processes underlying chromosome synapsis and recombination, as well as monoorientation of sister kinetochores in the first division, the key features distinguishing meiosis from mitosis and ensuring chromosome number reduction.